2022
DOI: 10.1007/s43069-022-00174-4
|View full text |Cite
|
Sign up to set email alerts
|

Colombian Origin Coffee Supply Chain Traceability by a Blockchain Implementation

Abstract: This exploratory study explains how to implement Blockchain technology for a supply chain by a proof of concept on Hyperledger Fabric, an open distributed ledger platform. This approach allowed to identify the feasibility and some implementation challenges, yield feedback, and exemplify one manner of tracing product origin using a distributed ledger technology. For this purpose, the case study of origin coffee is analyzed, given the relevance of traceability in this type of coffee and the cultural and economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The private database offers transparency in the coffee production supply chain to key stakeholders in coffee production. Although blockchain was shown to be effective in the digital traceability of coffee in an exploratory study, researchers found drawbacks to coffee production in Colombia, which may explain why the technology has not been locally adopted [35]. Specifically, manual labor by coffee growers and farmers is rarely shared or concerted, making it troublesome to have information integrity in the chain.…”
Section: Colombiamentioning
confidence: 99%
“…The private database offers transparency in the coffee production supply chain to key stakeholders in coffee production. Although blockchain was shown to be effective in the digital traceability of coffee in an exploratory study, researchers found drawbacks to coffee production in Colombia, which may explain why the technology has not been locally adopted [35]. Specifically, manual labor by coffee growers and farmers is rarely shared or concerted, making it troublesome to have information integrity in the chain.…”
Section: Colombiamentioning
confidence: 99%
“…To this end, the case study of origin coffee is analyzed, given the relevance of traceability in this type of coffee and the cultural and economic importance of this agricultural product in the Colombian context. In addition, the data stored on the Blockchain and some aspects of the technological architecture are discussed (Bettín-Díaz, 2022). 4.4 Distribution of scientific production by area of knowledge Figure5shows the distribution of the elaboration of scientific publications based on the area of knowledge through which the different research methodologies are implemented.…”
mentioning
confidence: 99%